Assessment of Development Results - Brazil - Programme des Nations Unies pour le Développement (United Nations, 2011)
This independent Assessment of Development Results in Brazil, conducted by the Evaluation Office of the United Nations Development Programme (UNDP), is part of a series of country-level evaluations. The evaluation examined the UNDP contribution to Brazil’s development from 2002 to 2010 and provides forward-looking recommendations that are useful for the formulation of the new UNDP country programme in Brazil.